Automated Urine Particle Analyzer UF-1000i Can Pre-Estimate the Treatment Response of Women’s Uncomplicated Urinary Tract Infections to Antibiotics - Shei-Dei Yang, Stephen; Chen, Yi-Sheng; Yang, Chun-Chun; chang, shang-jen (Urology Journal, 2021)
Purpose: To evaluate the ability of bacterial scatter diagrams generated from the automated urine particle analyzer (UF-1000i, Sysmex, Kobe, Japan) to pre-estimate the treatment efficacy of oral cefalexin in treating women with uncomplicated urinary tract infection (uUTI). Materials and Methods: Over 3 years, women 20-80 years old with symptoms suggestive of uUTI (Urinary Tract Infection Symptoms Assessment symptom score, ,UTISA > 3) and bacteriuria (bacterial count ≥ 100/uL) were enrolled. After informed consent, patients took cephalexin 500mg 4 times/day for 7 days. The voided urine specimens were classified into rods or cocci/mixed group automatically through the built-in software of the UF1000i. Patients were followed up with UTISA on the 3rd day after treatment and returned to the clinic on the 7th day and followed for additional UTISA and urine analysis. Symptom and laboratory improvement were defined as UTISA < 4 and bacterial count < 100/uL, respectively, on the 7th day. Results: Of 99 women (age: 49.91 ±15.32 years) eligible for analysis, 80 were classified as having urine that contained rods and 19 as cocci/mixed. Symptom improvement was observed in 62 women in the rods group and 11 women in the cocci/mixed group (p = 0.08). Laboratory improvement was noted in 64 women in the rods group and 10 women in the cocci/mixed group (p = 0.01). On day 7, treatment success with both symptom and laboratory improvement was more observed in rods than in cocci/mixed group (61.3% vs. 26.3%, p < 0.01). Conclusion: The automatic urine particle analyzer can pre-estimate the treatment response of antibiotics in women with uUTI.